Pengamanan Data Teks Menggunakan Algoritma DES Berbasis Android - Barany Fachri; Roy Martin Sembiring (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Android smartphone is certainly no stranger to the public and of course has spread widely to the world. Android smartphone has many applications in it and also has the function of each of these applications. One application that is commonly used is sending SMS, which functions as sending and receiving data quickly. SMS is a text message that at the time of sending has been limited and set its size, the size limit is 160 characters per SMS. But every use and use of SMS is certainly subject to shipping fees that have been determined from the operator. With this, security is one of the most important aspects to maintain the confidentiality and authenticity of the SMS messages so that they avoid being tapped, stolen or irresponsible. So it is very necessary to apply security in this SMS application that uses cryptographic DES (Data Encryption Standard) algorithm so that messages sent to their destinations can be kept confidential and authentic